How Does Monetary Policy Respond to Exchange Rate Movements? New International Evidence - Hilde C. Bjørnland; Jørn Inge Halvorsen (Norges Bank, 2008)
This paper analyzes how monetary policy responds to exchange rate movements in open economies, paying particular attention to the two-way interaction between monetary policy and exchange rate movements. We address this issue using a structural VAR model that is identified using a combination of sign and short-term (zero) restrictions. Our suggested identification scheme allows for a simultaneous reaction between the variables that are observed to respond intraday to news (the interest rate and the exchange rate), but maintains the recursive order for the traditional macroeconomic variables (GDP and inflation). Doing so, we find strong interaction between monetary policy and exchange rate variation. Our results suggest more theory consistency in the monetary policy responses than what has previously been reported in the literature.
hdl:11250/2497770
Keywords: C32; E52; F31; F41; 330; SVAR; Bayesian estimation; exchange rate; monetary policy; sign restrictions